(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
The influence of polyethylenglicole of various molecular mass on structural transformations of aqua soluble surface-active substance, sodium pentadecylsulfonate, has been investigated by methods of viscosimetry and light scattering in dependence of quantity of polymer in the system. It was established, that polyethylenglicole with molecular mass 2 000 and 40 000 has not influence on the structure of the system. Polyethylenglicole with molecular mass 4 000, 6 000 and 20 000 exhibits well-defined behavior of dependence of intrinsic viscosity on quantity of polymer. It was assumed, that changing the polyethylenglicole concentration in the system the compactization of micelle takes place due to changing the balance of hydrophobic-hydrophilic interactions. The change of appeared micelle mass and asymmetry coefficients which are established by the method of light scattering, has a simbate change with the dependence of intrinsic viscosity on the composition of mixture.